2012
DOI: 10.1021/jm3010724
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 3-Cyclopropylmethyl-7-(4-phenylpiperidin-1-yl)-8-trifluoromethyl[1,2,4]triazolo[4,3-a]pyridine (JNJ-42153605): A Positive Allosteric Modulator of the Metabotropic Glutamate 2 Receptor

Abstract: Advanced leads from a series of 1,2,4-triazolo[4,3-a]pyridines with mGlu2 receptor PAM activity are reported. By modification of the analogous imidazo[1,2-a]pyridine series, the newly reported leads have improved potency, in vitro ADMET, and hERG as well as good in vivo PK profile. The optimization of the series focused on improving metabolic stability while controlling lipophilicity by introducing small modifications to the scaffold substituents. Analysis of this series combined with our previously reported m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 43 publications
0
50
1
Order By: Relevance
“…A subsequent publication detailed continued optimization within this series in the context of a 4-phenylpiperidine substituent at the C 7 position (Figure 5) and described the discovery of JNJ-42153605 ( 61 ). 273 In this case, a triazolopyridine core was used as a less lipophilic alternative to the imidazopyridine. Critical to the success of this effort was the identification of the trifluoromethyl group at the C 8 position as an optimal substituent for mGlu 2 PAM activity.…”
Section: 2 Allosteric Modulators Of the Mglu2 And Mglu3 Receptorsmentioning
confidence: 99%
“…A subsequent publication detailed continued optimization within this series in the context of a 4-phenylpiperidine substituent at the C 7 position (Figure 5) and described the discovery of JNJ-42153605 ( 61 ). 273 In this case, a triazolopyridine core was used as a less lipophilic alternative to the imidazopyridine. Critical to the success of this effort was the identification of the trifluoromethyl group at the C 8 position as an optimal substituent for mGlu 2 PAM activity.…”
Section: 2 Allosteric Modulators Of the Mglu2 And Mglu3 Receptorsmentioning
confidence: 99%
“…With stronger metabolic stability, another PAM, JNJ-42153605 effectively reversed PCP-induced hyperlocomotion (Cid et al, 2012). In addition, it has been reported that JNJ-40068782 was able to potentiate the binding of mGluR2/3 agonists (Lavreysen et al, 2013).…”
Section: Overview Of More Selective Mglur2/3 Agonists: Potentials mentioning
confidence: 99%
“…In an attempt to differentiate between various compounds and mechanisms of action, we compared the effects of JNJ‐40411813, the mGlu2/3 receptor agonist LY404039, the selective mGlu2 PAM JNJ‐42153605 (Cid et al. ) and the 5HT 2A receptor antagonist ritanserin in animal models for antipsychotic activity and side effects. Since the preclinical observations with JNJ‐40411813 have led to its selection for clinical studies, the results are also discussed in light of clinical data available for this molecule.…”
Section: Introductionmentioning
confidence: 99%